3D Printing Cultures, Politics and Hackerspaces - Savvides, Leandros (Digital activism and society., 2021)
This book appreciably contributes to growing debates within Science and Technology Studies concerned with cultural politics, the emergence of citizen science and civil society interventions in shaping technology. By drawing on fieldwork data, Savvides examines the bourgeoning 3D printing culture in Hackerspaces, Makerspaces and Fab Labs.